MTA-cooperative PRMT5 inhibitors from cofactor-directed DNA-encoded library screens - Jan Andersson; Sanne Cowland; Mikkel Vestergaard; Yajing Yang; Siyuan Liu; Xie Fang; Susmith Mukund; Sudipa Ghimire-Rijal; Chris Carter; Grace Chung; Tomas Jacso; Ian Sarvary; et al. (Proceedings of the National Academy of Sciences, 2025)
Methylthioadenosine phosphorylase ( MTAP ) gene deletions are frequent in human cancers. Loss of MTAP leads to significantly increased cellular levels of methylthioadenosine (MTA), a cellular metabolite and specific inhibitor of the cell-essential enzyme Protein Arginine Methyltransferase-5 (PRMT5). Using a cofactor-directed screening strategy and DNA-encoded libraries, we identify a class of PRMT5 inhibitors that cooperatively inhibit PRMT5 in the presence of MTA. An optimized inhibitor, AM-9934, selectively inhibits PRMT5 in MTAP -deleted cells and in transplanted tumors while sparing MTAP -expressing counterparts, leading to specific suppression of viability in MTAP -deleted cells. Structural studies show that AM-9934 occupies the arginine substrate pocket of MTA-bound PRMT5. This study introduces a broadly applicable method for directed DNA-encoded library screening toward a desired mechanistic outcome and highlights MTA-selective PRMT5 inhibition as an attractive therapeutic strategy with a potentially broad therapeutic index in patients with MTAP -deleted cancers.